Surgical conversion early after failed percutaneous repair with the Mitraclip system - Takahashi, Hiroaki; Rauch, Helmut; Karck, Matthias; Fritz, Markus (European journal of cardio-thoracic surgery, 2012)
A 72-year-old man underwent mitral valve (MV) replacement after failed percutaneous MV repair with the MitraClip (Abbott Vascular, USA) (Fig. 1). Our report dem